Meningkatkan Kompetensi Masyarakat Pesisir dalam Budidaya Kepiting Bakau: Penerapan Sistem Apartemen dan RAS di Desa Persiapan Empol, Sekotong, Lombok Barat - Setyono, Bagus Dwi Hari; Junaidi, Muhammad; Diniariwisan, Damai; Sumsanto, Muhammad; Cokrowati, Nunik; Saputra, Ardyen (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This community service project was conducted in Persiapan Empol Village, Sekotong District, West Lombok Regency, to enhance the knowledge and skills of local communities in mud crab (Scylla spp.) farming using the apartment system and recirculating aquaculture system (RAS). The village is rich in natural resources, particularly in fisheries, but limited knowledge has been a major obstacle in developing aquaculture practices. The method used in this project was a demonstration plot involving 15 members of the "Sopoq Angen" mud crab farming group. The activities included constructing an apartment system from used jerry cans, installing RAS, and monitoring water quality and crab growth over 3 months. The results showed a significant improvement in the partners' understanding and skills, with crab survival rates reaching 96% and good growth in body weight. The apartment system and RAS proved effective in supporting the success of mangrove crab farming in this coastal area.